Evaluation of nutritional and health benefits of oyster mushroom. - Jaziya S (Department of Home Science, College of Agriculture, 2011)
“Evaluation of nutritional quality and health benefits of oyster mushroom” (Pleurotus florida) was a comprehensive study undertaken to determine the nutritional quality, nutrient losses during processing and also to investigate the impact of mushroom supplement on the blood profile of the subjects with specific disease condition.